2008
DOI: 10.1021/ja8026373
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular Self-Assembly of Amphiphiles on Carbon Nanotubes: A Versatile Strategy for the Construction of CNT/Metal Nanohybrids, Application to Electrocatalysis

Abstract: Homogeneous coating of carbon nanotubes with metallic nanoparticles was achieved using supramolecular auto-organization of amphiphilic molecules as template. The resulting Pd nanoparticles/carbon nanotube nanohybrids were then evaluated in electrocatalysis experiments, showing superior activity in ethanol oxidation compared to analogous systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
76
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(79 citation statements)
references
References 18 publications
3
76
0
Order By: Relevance
“…On the other hand, on multi-walled CNTs, single-tailed ionic surfactants have been reported to form helical striations. 16,17 Also on multi-walled CNTs, Richard et al speculated that the various helical striations they observed SDS to produce follow the underlying carbon network. 16 Furthermore, single-tailed lipids, such as lysophosphadidylcholine (LPC) and lysophosphatidylglycerol have been also found to form striations on CNTs.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, on multi-walled CNTs, single-tailed ionic surfactants have been reported to form helical striations. 16,17 Also on multi-walled CNTs, Richard et al speculated that the various helical striations they observed SDS to produce follow the underlying carbon network. 16 Furthermore, single-tailed lipids, such as lysophosphadidylcholine (LPC) and lysophosphatidylglycerol have been also found to form striations on CNTs.…”
Section: Introductionmentioning
confidence: 99%
“…New multifunctional nanoparticle-nanotube hybrid systems, due to their unique and superior properties compared with their pure counterparts, increasingly forming the foundation of transformational developments in areas as diverse as electronics, photonics, catalysis, biotechnology, and energy storage among many other applications (Wu et al 2011;Mackiewicz et al 2008;Georgakilas et al 2007;Kong et al 2007;Li et al 2009). Single-walled aluminosilicate nanotubes (AlSiNTs) are excellent candidates for fabricating various functional nanohybrid materials due to their well-defined one-dimensional structure (Yucelen et al 2011;Thill et al 2012), vast range of tunable compositions (Avellan et al 2014), functionalizable surfaces (Kang et al 2011), attainability in pure form without a catalyst (Yucelen et al 2011), and ability to readily form hydrogels, transparent films, powders, and coatings (Jiravanichanun et al 2011;Kuroda et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In order to enhance the efficiency of DMFCs and to accelerate the electron transfer rate, carbon nanotubes (CNTs) with high specific surface areas, electrical conductivities, and chemical stability have been used as supports for the preparation of Pt nanoparticles (NPs)/CNT nanohybrids [3][4][5][6][7]. However, pristine CNTs have insufficient binding sites to anchor Pt ions (precursors) and NPs, which lead to poor dispersion, aggregation of NPs [8], inefficient catalytic activity, poor reproducibility, and poor durability of Pt NPs/CNT nanohybrids.…”
Section: Introductionmentioning
confidence: 99%